Child laws: containing acts, rules, charters, conventions, policies & guidelines for children & juvenile justice (New Delhi, 2012)
This book talks about Child laws: containing acts, rules, charters, conventions, policies & guidelines for children & juvenile justice
Keywords: Children rights